Peningkatan Hasil Belajar Siswa Kelas IV Melalui Model Think Pair Share Berbantuan Media Puzzle - Siti Nur Wahyu Ahmadah; Deka Setiawan; Sekar Dwi Ardianti (Universitas Pendidikan Indonesia Kampus Serang, 2020)
Think Pair Share model can give students more time to think, answer, respond and through this method the teaching materials presentation will be more alive by discussing solving a problem with their partners. This study tried to promote the use of Think Pair Share models aided by puzzle media to solve learning problems of fourth grade of State Elementary School 02 Kebonsawahan in theme of The Beauty of Diversity in My Country. This study aimed to describe the improvement of student learning outcomes through the Think Pair Share learning model and puzzle media in Civic Education and Indonesian Language content through two cycles of classroom action research. The results showed an increase after learning by using Think Pair Share learning models assisted by puzzle media in aspect of knowledge attitude and skill. Students’ learning outcomes in aspects of knowledge increased from the cycle I by an average of 69.1 with 64% classical completeness (need guidance) to be an average of 86.1 with 89% classical completeness (good) in cycle II. While in attitude aspects, students’ learning outcomes of cycle I which gained a percentage of 72.45% (need guidance) increased in the cycle II by 83.63% (good). The learning outcomes of students in the skills aspect also perfomed an improvement from a percentage of 73.83% (need guidance) in cycle I to be a percentage of 84.13% (good) in cycle II. This result indicated that the TPS model effectively solve the problems of inactive learning in elementary school level.